ASSIGNING STUDENTS TO LISTEN TO THE ENGLISH NEWS IN LISTENING COURSE - Adnan, Aryuliva (English Department FBS UNP, 2013)
This paper presents one of the ways to improve studentsâ€™ listening ability in Listening 2 Course. At the English Department of Universitas Negeri Padang listening skill is taught in three different subjects, Listening 1, Listening 2 and Advanced Listening. Listening 2, provides students with the materials of oral communication by English native speakers and English nonnative speakers. Looking at the materials used for Listening 2, it seems that the book does not have enough tasks for the students for it has only two or three tasks for each unit. Those tasks are done in the classroom, and there is no task for homework. Learning Listening as a language skill needs practice inside and outside the classroom.Â To overcome the lack of task for Listening subject, assigning students to listen to the English news is one of the ways that can be done by the teachers. By assigning students to listen to the English news, whether radio or TV news, will give them real experiences in understanding spoken language. To ensure the students listen to the news, they have to record and submit the news and the tape script of the news as well Keywords: assigning, English radio/TV news